Initial treatment is associated with improved survival and end-of-life outcomes for patients with pancreatic cancer: a cohort study - Khan, Rishad; Salim, Misbah; Tanuseputro, Peter; Hsu, Amy T.; Coburn, Natalie; Hallet, Julie; Talarico, Robert; James, Paul D. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background We describe the association between initial treatment and end-of-life (EOL) outcomes among patients with pancreatic ductal adenocarcinoma (PDAC). Methods This population-based cohort study included patients with PDAC who died from April 2010–December 2017 in Ontario, Canada using administrative databases. We used multivariable models to explore the association between index cancer treatment (no cancer-directed therapy, radiation, chemotherapy, surgery alone, and surgery and chemotherapy), and primary (mortality, healthcare encounters and palliative care) and secondary outcomes (location of death, hospitalizations, and receipt of chemotherapy within the last 30 days of life). Results In our cohort (N = 9950), 56% received no cancer-directed therapy, 5% underwent radiation, 27% underwent chemotherapy, 7% underwent surgery alone, and 6% underwent surgery and chemotherapy. Compared to no cancer-directed therapy, radiation therapy (HR = 0.63), chemotherapy (HR = 0.43) surgery alone (HR = 0.32), and surgery and chemotherapy (HR = 0.23) were all associated with decreased mortality. Radiation (AMD = − 3.64), chemotherapy (AMD = -6.35), surgery alone (AMD = -6.91), and surgery and chemotherapy (AMD = -6.74) were all associated with fewer healthcare encounters per 30 days in the last 6 months of life. Chemotherapy (AMD = -1.57), surgery alone (AMD = -1.65), and surgery and chemotherapy (AMD = -1.67) were associated with fewer palliative care visits (all p-values for estimates above < 0.05). Treatment groups were associated with lower odds of institutional death and hospitalization at EOL, and higher odds of chemotherapy at EOL. Conclusions Receiving cancer-directed therapies was associated with higher survival, fewer healthcare visits, lower odds of dying in an institution and hospitalization at EOL, fewer palliative care visits, and higher odds of receiving chemotherapy at EOL.